Effectiveness of voc absorption between Rhapis excelsa (Thunb.) A. Henry, Nephrolepis exaltata (L.) and Dracaena fragrans (L.) in small rooms - Ghazalli, Aini Jasmin (2012)
Recently, airtight envelope building system has become popular in order to help reduce heating and cooling loads. The change in building design was to improve energy efficiency resulting modern structures to be more airtight. Volatile organic compounds (VOC) are one of the most mentioned indoor pollutant and exposures to it can cause a series of effect towards human health. There are numerous methods that can help rid off indoor pollutants. However, combination of several methods may seem more efficient in ensuring good indoor air quality. This study is aimed to examine which among three selected tropical indoor plants to be the best in absorbing VOC in a small office space. The reading of VOC was recorded using Aeroqual Model S500 VOC Gas Detector. Data was collected for four hours and the VOC source was oil-paint painted on a panel measuring 0.05 x 0.05 m. The plants used in this study were Rhapis excelsa (Thunb.) A. Henry, Nephrolepis exaltata (L.) and Dracaena fragrans (L.). The result showed there was significance difference within the plant species. There was also significant difference within the number of pots used in the room. From the experiment, among three plants used in this study,R. excelsa has been identified as the best indoor plant to absorb VOC with the highest decrement when using six pots. The result of this finding strengthens previous research about the plants’ capability and effectiveness in filtering the polluted indoor air.